Cdc42 defect reveals insights into microvilli organization and function in T cell immunity - Won-Chang Soh; Sang-Moo Park; Jeong-Su Park; Hatice Karabulut; Hee-Tae Kang; Sun-Kyoung Kang; Min-Sang Kim; Jihwan Park; Sunjae Lee; Hye-Ran Kim; Chang-Duk Jun (Proceedings of the National Academy of Sciences, 2025)
Microvilli on T cells differ from those on epithelial cells, exhibiting filopodia-like characteristics that facilitate the clustering of molecules essential for sensing and cell migration. Recently, they have also been recognized as the structures from which T cell immunological synaptosomes (TIS) are released. In this study, we examined a key determinant of microvilli organization during T cell development and explored the functional roles of these structures, particularly in relation to T cell behaviors. During thymocyte maturation, single-positive thymocytes were found to develop more and longer microvilli than double-positive thymocytes. However, the deletion or inhibition of Cdc42, a small Rho family protein, significantly reduced both the number and length of microvilli in single-positive thymocytes, leading to decreased cell mass. This reduction in microvilli correlates with a decrease in antigen recognition, leading to diminished T cell activation and adhesion, as well as reduced TIS production, while intrinsic migratory properties remain unaffected. These findings highlight the filopodia-like characteristics of T cell microvilli. In this context, Cdc42 contributes significantly to microvilli formation, thereby shaping T cell function.